VR Math Quiz: Virtual Reality Game-Based Application in Primary School Mathematics Subject - Hazizan, Nur Aliaa (IRC, 2019)
Game-based learning allows leveraging on young learner preference towards playing games to turn games into tools for learning. The integrating of VR technology with gamebased learning in education has a higher potential to increase the motivation and interest of students. According to the Malaysia Education Statistic 2018 by the Ministry of Education, it shows that the quality of STEM education in schools today is not fulfilling the needs of the workforce in STEM fields. Studies show that the lack of good teaching and learning approaches, and the lack of student’s interest in STEM education are the factors of declining of the quality in STEM education in Malaysia. By developing a suitable VR game-based application to teach students in STEM education, the student would be able to learn interactively. Moreover, they may be able to explore things by their movements instead of just sitting in the classroom. They can see the environment in 3D vision by using VR tools which are VR headset. Several objectives have been identified which are to investigate the suitable theories that can relate with game-based application in Virtual Reality, to develop an appropriate game-based application that can be implemented in Virtual Reality and to conduct the user testing. The target users for the study is primary school students who are in Year 4, 5, and 6. The age of the targeted students between 10-12 years old. The research is focusing on primary school students in Mathematics subject. The game-based application in Virtual Reality generally target these students in the subtopics according to the current syllabus as per outlined by the Ministry of Education in Malaysia. This gaming application with the implementation of Virtual Reality will be run using HTC VIVE Virtual Reality and will be developed using the Unity gaming engine.